A community based cross sectional study on prevalence of iodine deficiency disorders among 6-12 years children of a district of North Karnataka - Sonavane, Rekha S.; Mayappanavar, Ramesh H.; K. R., Ananthachari; Roy, Subarna; Prasad U., Venkateswara; Byakod, Mahesh; Mudaraddi, Roshan; K., Shilpa (International Journal Of Community Medicine And Public Health, 2017)
Background: Iodine deficiency is the major preventable cause of irreversible mental retardation in the world with nearly 2 billion people with iodine deficiency disorders (IDD).In India district level surveys conducted in 2006 in 324 districts have revealed that IDD is a major public health problem in 263 districts that is total goitre prevalence rate of more than 10% in the population. Methods: The survey was conducted from November 2016 to January 2017, after obtaining permission from Institutional Ethical Committee, using population proportionate to size (PPS) sampling method among of 6-12 years children. In the selected villages, primary schools were visited and a sample of 90 children was selected and was examined after consent from school authority. Prevalence of goitre was assessed and graded by standard palpation method. In few selected children urine and house hold salts are examined. Results: The prevalence of goitre among the 6 to 12 years children was found to be 22.78%. There was not much difference in prevalence of goitre in females compared to males in all the age groups and prevalence of goitre was observed to increase with age, which was found to be statistically significant (p=0.00001). Conclusions: Prevalence of iodine deficiency is significantly high and higher prevalence was found with increasing age.